2018
DOI: 10.1021/acs.inorgchem.8b01983
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Structure and Luminescence Properties of Undoped and Eu3+-Doped La2Hf2O7 Nanoparticles Prepared with Different Coprecipitating pH Values through Experimental and Theoretical Studies

Abstract: Understanding the structure-property relationship and optimizing properties of phosphors for use in lighting and scintillation fields is an important materials challenge. In this work, we investigated the effects of the pH value of the coprecipitating solution adjusted by the concentration of NHOH(aq) on the structure and optical properties of the obtained LaHfO nanoparticles (NPs). The obtained NPs stabilize in the ideal pyrochlore structure, but the extent of ordering increased with an increase in the pH val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 77 publications
6
58
0
Order By: Relevance
“…Several parameters affect the morphology and size of NPs synthesized by the molten salt method. In our previous investigation, we demonstrated that the level of OH − concentration during the synthesis of the precursor affects the size of the synthesized NPs without manipulating the molten salt synthesis time and temperature [7]. For the LHOE system, as the concentration of OH − increased, the size of the particles increases proportionally [7].…”
Section: Characterization Of the Lhoe Npsmentioning
confidence: 98%
See 4 more Smart Citations
“…Several parameters affect the morphology and size of NPs synthesized by the molten salt method. In our previous investigation, we demonstrated that the level of OH − concentration during the synthesis of the precursor affects the size of the synthesized NPs without manipulating the molten salt synthesis time and temperature [7]. For the LHOE system, as the concentration of OH − increased, the size of the particles increases proportionally [7].…”
Section: Characterization Of the Lhoe Npsmentioning
confidence: 98%
“…N, N-Dimethylacetamide (DMA, ≥ 99%), acetone (≥ 99.5%), PVDF (average molecular weight of 534,000) were purchased from Sigma-Aldrich USA. The LHOE NPs were synthesized by a molten salt method as reported in our previous publications [5][6][7]10]. 1.0 wt% of LHOE NPs and 22wt%of PVDF were mixed in a 77 wt% solvent (50:50 weight percentage ratio of acetone: DMA) by stirring with a magnet bead for 2 h. The LHOE-PVDF nanocomposite films were fabricated through a drop-casting technique by dropping 1 mL of the solution on a planar surface of a watch glass.…”
Section: Synthesismentioning
confidence: 99%
See 3 more Smart Citations